Measuring the Operative Treatment Effect in End-Stage Ankle Arthritis: Are We Asking the Right Questions? A COFAS Multicenter Study. (October 2017) - Wing, Kevin J.; Chapinal, Nuria; Coe, Marcus P.; Daniels, Timothy R.; Glazebrook, Mark; Dryden, Peter; Younger, Alastair; Penner, Murray J.; Sutherland, Jason M.
Background: Foot and ankle surgeons are increasingly relying on patient-reported outcome measures (PROMs) such as the Ankle Osteoarthritis Scale (AOS) to evaluate treatment options. The objectives of this retrospective cohort study were 2-fold: (1) to examine the AOS instrument using psychometric analysis and (2) to revise the questions on the AOS to improve the effect of questions on the score and remove redundancies. Methods: Pre- and postoperative patient scores were obtained from AOS questionnaires in the COFAS Prospective Ankle Reconstruction Database, a cohort of patients operatively treated for end-stage ankle arthritis. A split-sample approach was used to evaluate the AOS and to propose a revised instrument. Results: A total of 380 patients who had been treated with total ankle replacement or ankle arthrodesis were prospectively followed to the 2-year postoperative time point. Correlation analysis demonstrated that a number of questions on the AOS were highly correlated with other similar questions, frequently incomplete, or showed little variation between respondents. Eight of the original AOS questions were retained in the newly proposed Ankle Arthritis Score (AAS) [3 from the AOS Pain subscale and 5 from the AOS Disability subscale]. Principal components analysis (PCA) showed that these questions equally clustered into 2 domains in AAS: Basic Activity and Advanced Activity. Conclusions: The AAS is shorter and has improved psychometric properties as compared to the AOS. Further investigation is required to better characterize the clinical utility of this proposed new patient-reported outcome score. Level of Evidence: Level III, retrospective cohort study.